Orlistat and ezetimibe could differently alleviate the high-fat diet-induced obesity phenotype by modulating the gut microbiota - Jin, Jin; Wang, Jiani; Cheng, Ruyue; Ren, Yan; Miao, Zhonghua; Luo, Yating; Zhou, Qingqing; Xue, Yigui; Shen, Xi; He, Fang; Tian, Haoming (Frontiers in Microbiology, 2022)
This study aimed to conduct to evaluate the possible anti-obesity effects of orlistat and ezetimibe against and know how they might alter gut microbiota and short chain fatty acids (SCFAs) of the mice with a high-fat diet (HFD) inducted obesity. Eighty male, specific pathogen-free C57BL/6J mice aged 3 weeks were divided into four groups (n=20). The NCD group was fed with a normal diet, and the HFD, HFD+ORL, and HFD+EZE groups were fed with HFD for 20 weeks. From the 13th week, the HFD+ORL and HFD+EZE groups were administered with orlistat and ezetimibe, respectively. The glucose and lipid metabolism of the tested mice were tested by analyzing blood biochemical during intervention. Furthermore, the changes in structure of the fecal microbiota and the fecal SCFAs content were analyzed by 16S rRNA sequencing and the gas chromatography - mass spectrometry, respectively. HFD induced the obesity phenotype in mice. Compared to the HFD group, the body weight, visceral fat-to-body weight ratio, serum total cholesterol (TC), high-density lipoprotein-cholesterol (HDL-C), and oral glucose tolerance test (OGTT) of the HFD+ORL group significantly decreased, whereas fecal butyric acid levels significantly increased. Ezetimibe intervention significantly reduced the OGTT and serum TC and HDL-C levels only. The -diversity of the gut microbiota significantly decreased after intervention with orlistat and ezetimibe. Orlistat altered the relative abundance of some bacteria in the fecal. Firmicutes, Alistipes and Desulfovibrio decreased, whereas Verrucomicrobia and Akkermansia significantly increased. Ezetimibe caused changes only in some low-abundance bacteria, as manifested by a decrease in Proteobacteria and Desulfovibrio, and an increase in Bacteroides. Orlistat and ezetimibe can characteristically influence the body weight and serum lipid metabolism, and glucolipid levels of diet induced obese mice accompanied with different changes in gut microbiota and SCFAs. These results suggest that the two drugs might exert its own specific anti-obesity effects by modulating the gut microbiota with different manner. The enhanced health promoting effect of orlistat might results from its stronger ability to gut microbiota and SCFAs, at least partly.